1983
DOI: 10.2134/agronj1983.00021962007500030020x
|View full text |Cite
|
Sign up to set email alerts
|

Fertilizer Application and Irrigation Management of Broccoli Production and Fertilizer Use Efficiency1

Abstract: Fertilizer and irrigation must be managed for efficient resource use and preservation of environmental quality as well as maximum production. Two furrow irrigation experiments growing broccoli (Brassica oleracea) were conducted. The first consisted of three N rates (90, 180, and 270 kg/ha), two irrigation treatments (replenishment of water lost by evapotranspiration and evapotranspiration plus 30%), and two N application procedures (application to the soil and in the irrigation water) on a sandy loam soil (coa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
30
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 4 publications
5
30
0
Order By: Relevance
“…4). These results are similar to Letey et al (1983) and Zebarth et al (1995). A significant nitrogen rate by year interaction for NUE was observed (P 00.0001).…”
Section: Plant Growth and Tissue Nitrogen Analysissupporting
confidence: 92%
See 2 more Smart Citations
“…4). These results are similar to Letey et al (1983) and Zebarth et al (1995). A significant nitrogen rate by year interaction for NUE was observed (P 00.0001).…”
Section: Plant Growth and Tissue Nitrogen Analysissupporting
confidence: 92%
“…Researchers have also attempted to measure nitrogen movement and loss in the soil. In these studies, very little nitrate was presumed lost during the growing season, and the majority of soil nitrate remained in the top 15 to 30 cm of the soil at harvest (Letey et al 1983;Kowalenko and Hall 1987;Zebarth et al 1995;Thompson et al 2002b).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In most studies that included rates up to 336 kg N ha -1 , the response was positive and linear or quadratic (Cutcliffe et al 1968;Cutcliffe et al 1971;Hipp 1974;Letey et al 1983;Beverly et al 1986;Kowalenko and Hall 1987b;Shattuck and Shelp 1987;Tremblay 1989), although two studies found minimal or no yield response to N fertilization (Bracy et al 1995;Kahn et al 1991). In studies that included higher N rates (Greenwood et al 1980;Zebarth et al 1995) or low soil moisture (Beverly et al 1986), a maximum yield response was found beyond which yield declined with additional N applied.…”
mentioning
confidence: 99%
“…Generally, N-fertilization studies have also shown that broccoli plants are efficient at accumulating N. In studies using N-fertilizer rates up to 250 kg ha -1 , the crop accumulated more N than was applied as fertilizer (Magnifico et al 1979;Letey et al 1983;Kowalenko and Hall 1987b;Shelp and Liu 1992;Zebarth et al 1995). Zebarth et al (1995) applied N-fertilizer at rates up to 625 kg ha -1 and found that N accumulation by the crop was maximized when about 500 kg N ha -1 was applied and ranged from 345 to 465 kg ha -1 , depending on the cropping season.…”
mentioning
confidence: 99%